PENERAPAN NILAI-NILAI PANCASILA DALAM PRAKTIK BISNIS MELALUI ANALISIS PERMASALAHAN SUMBER DAYA MANUSIA DAN PROGRAM PENGEMBANGAN PADA UMKM KEDAI TOEAN HAN: Application Of Pancasila Values In Business Practices through The Analysis of Human Resource Problems and Development Programs at Small And Medium Enterprises Kedai Toean Han - Fidda Nuraini Nabilah; Nazara Nathania; Siti Aulia Septiyani; Nurhiyah (Jurnal Manajemen, 2026)
Pancasila plays an important role in shaping business values and ethics in Indonesia, including in the Micro, Small, and Medium Enterprises (MSME) sector. However, its implementation still faces obstacles, especially in human resource management. This study aims to analyze the problems currently being experienced, as well as employee development programs at Kedai Toean Han MSMEs through the perspective of Pancasila values. The research uses a qualitative approach with in-depth interviews with employees. The results of the study show that there are challenges in HR management related to discipline, work motivation, and communication, as well as efforts to develop values based on justice, and humanity. The application of Pancasila in MSME business practices can strengthen work ethics, improve interpersonal relationships, and support business sustainability through HR development based on national values.